C. Bradley Scharf: Politics and Change in East Germany: An Evaluation of Socialist Democracy - Peter W Krawutschke (GDR Bulletin, 1985)
Boulder, Colo.: Westview, 1984. xii + 219 p., 27.00, 11.95 paper.